Model Komunikasi Krisis Berbasis Nilai Islam di Pondok Pesantren Attibyan Deli Serdang - Suhendri Suhendri; Hafsah Juni Batubara; Wahyunisa Wahyunisa (Academic Journal of Da'wa and Communication, 2025)
This study aims to formulate a model of Islamic value-based crisis communication in an Islamic boarding school through a case study at Pondok Pesantren Attibyan, Deli Serdang. Using a qualitative approach with in-depth interviews, observation, and documentation, this research examines how leaders, administrators, teachers, and students manage information and respond to crisis situations. The findings reveal that crisis communication at Attibyan is structured hierarchically while remaining consultative, grounded in Islamic values such as tabayyun (verification) and amanah (accountability). An important contextual finding is that students are not allowed to use personal mobile phones within the pesantren environment. As a result, digital communication is centrally managed by the pesantren authorities, making information control more structured but also creating challenges in external communication speed. The study identifies a five-stage crisis communication model: early detection, internal verification, message formulation, controlled publication through official channels, and evaluation-recovery. Digital media are used selectively by the management for clarification and public education with an ethical and non-defensive tone. Key challenges include limited digital literacy among stakeholders and the absence of formal written procedures. This research contributes to the development of Islamic crisis communication models by integrating religious values with modern communication management practices in the context of pesantren.